A note on firms' strategic behaviour during an IPO - Pia Weiss; Stefan Mai (Universität zu Köln, Institut für Wirtschaftspolitik (iwp), 2002)
When potential shareholders cannot observe the business conditions of the firms, the latter desiring to acquire capital by an IPO and operating under less favourable business conditions have a strong incentive to appear more successful.
Keywords: D82; 330; IPO; asymmetric information; signalling game; Wertpapieremission; Asymmetrische Information; Signalling; Unternehmensentwicklung; Theorie